Effect of High Intensity Pulsed Ion Beam of Carbon on Subsurface Layers of Zirconia Ceramics; Advanced Materials Research; Vol. 1085 : Prospects of Fundamental Sciences Development (PFSD-2014) - Surzhikov A. P. Anatoly Petrovich; Vasiljev I. P. Ivan Petrovich; Vaytulevich (Vaitulevich) E. A. Elena Anatolievna; Frangulyan (Franguljyan) Т. S. Tamara Semenovna; Chernyavski (Chernyavskiy) A. V. Aleksandr Viktorovich (2015, 2015)
Title screen